THE ACCOUNTING IDENTIFICATION OF INTANGIBLE ASSETS IN FORMATION OF ECONOMIC SECURITY OF THE ENTERPRISE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article gives a theoretical generalization of the influence of intangible assets on the economic security of the enterprise. The following economic notions are considered as "intangible assets" and "economic safety of the enterprise".As a result of the conducted scientific research, the following definition of the essence of the concept was formulated: the economic security of the enterprise - is such an existing financial and economic state of the assets of the enterprise, which guarantees their protection, the possibility of the most effective use, sustainable growth of their value.The actual definition of the intangible assets of the enterprise as a part of the intellectual capital properly identified, recorded and can be used to profit, the formation of long-term competitive advantages and increase the market value of the enterprise.The advantages and disadvantages of the main approaches to the identification and classification of intangible assets of the enterprise are explored.The bases of accounting identification of intangible assets as part of the intellectual capital of the enterprise are determined.Improved accounting and information provision of certain structural elements of intellectual capital that can be used to develop the human and structural resources of the enterprise in the long run and to provide full information on the costs of human capital development, which is especially important for those enterprises in whose activities knowledge and the competence of the personnel play a crucial role and determine the success of their activities.At the same time, the proper accounting and information provision of the formation and use of intellectual capital helps to understand how the enterprise will achieve its goals; displaying in the financial statements information about the results of the formation and use of intellectual capital, managers bring users to the long-term perspective of the company, that is, the complete accounting and information provision of intellectual capital operations enables the demonstration of the long-term aspect of current activity.